1981
DOI: 10.1149/1.2127403
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Corrosion of Copper and Silver

Abstract: The corrosion rate of copper in laboratory tests is shown to be a sensitive function of relative humidity, sulfur dioxide, hydrogen sulfide, ozone, hydrogen chloride, and chlorine concentrations. Observed indoor corrosion rates obey log normal statistics over the field population of this study. Also, the observed indoor rates correlate reasonably well with the measured reduced sulfur concentrations ( H2S , S8 ). The corrosion rate of silver is shown not to be humidity dependent. Hydrogen sulfide, ozone, chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
101
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(102 citation statements)
references
References 13 publications
(27 reference statements)
1
101
0
Order By: Relevance
“…The experimental data of the sulfurization test are collected and summarized in Table 4. In the literature [28], the reaction between silver and sulfur-based corrosion gas has a linearly time dependent relationship. Our experimental data of pure silver, (Ag)-9.5In and (Ag)-19In agrees with this linear relationship, and can be fit well into linear curves, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental data of the sulfurization test are collected and summarized in Table 4. In the literature [28], the reaction between silver and sulfur-based corrosion gas has a linearly time dependent relationship. Our experimental data of pure silver, (Ag)-9.5In and (Ag)-19In agrees with this linear relationship, and can be fit well into linear curves, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the sterling standard stipulates a 7.5 % copper concentration. Unlike other precious metals such as gold and platinum, silver is known to tarnish with time forming Ag 2 S when exposed to low concentrations (<1 ppb) of H 2 S in ambient environments [1][2][3]. While Ag 2 S is the main component in silver tarnish, sulfate, chloride, oxide, and oxygenated carbon species can also be present [4].…”
Section: Introductionmentioning
confidence: 99%
“…The density of Al 2 O 3 ALD films (3.0-2.5 g/cm 3 , depending on deposition temperature) is at least 1.5 times greater than the density of nitrocellulose (1.6 g/cm 3 , depending on the nitrogen content), creating better barriers that slow the rate of gas diffusion [30,31]. For applications in cultural heritage, the thickness of a barrier film involves a tradeoff; a thick barrier film results in a long diffusion path for corrosive gases, while thicker films tend to more profoundly affect the optical properties and visual appearance of the film.…”
Section: Introductionmentioning
confidence: 99%
“…Also Ag 2 SO 4 as corrosion product was observed on silver coupons in field exposure [13] although the studies indicated that Silver sulfate (Ag 2 SO 4 ) forms only in artificially high levels of sulfur dioxide [14] [15].…”
mentioning
confidence: 99%
“…Silver is sensitive to chloride (Cl − ) and silver chloride will be formed as a result of the reaction [10] [11] [12] [15] [16] [17]. Also this does not agree with results revealed that silver chloride compound was not identified on surface film of silver coupons after the exposure in an ASTM B117 salt spray chamber [18] and this compatibility with previous studies mentioned that silver does not react directly with chlorine gas and the presence of silver chloride as corrosion product due to burial in a chloride rich environment [19] [20].…”
mentioning
confidence: 99%